2015
DOI: 10.1140/epjp/i2015-15140-3
|View full text |Cite
|
Sign up to set email alerts
|

Exact solutions of a two-dimensional Kemmer oscillator in the gravitational field of cosmic string

Abstract: The two dimensional Kemmer oscillator under the influence of the gravitational field produced by a topology such as the cosmic string spacetime and in the presence of a uniform magnetic field as well as without magnetic field are investigated. The eigensolutions of our problem have been found by using the generalized parametric Nikiforov-Uvarov (NU) method, and the influence of the cosmic string space-time on the energy spectrum has been analyzed. We show that the dependence of the energy levels of the quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…It is known as a conical singularity [5]. Interesting works [6][7][8][9][10][11][12][13][14][15][16][17] have explored this topological characteristic of the cosmic string with the purpose of searching for analogues of the Aharonov-Bohm effect [18,19]. It is worth clarifying that Peshkin and Tonomura [20] showed that if a quantum particle is confined to move in a circular ring of radius R and there is a solenoid (extremely long) of radius a < R, then, the angular momentum quantum number is modified by l eff = l − eΦ/2π (where Φ is the magnetic flux through the solenoid and e is the electric charge).…”
Section: Introductionmentioning
confidence: 99%
“…It is known as a conical singularity [5]. Interesting works [6][7][8][9][10][11][12][13][14][15][16][17] have explored this topological characteristic of the cosmic string with the purpose of searching for analogues of the Aharonov-Bohm effect [18,19]. It is worth clarifying that Peshkin and Tonomura [20] showed that if a quantum particle is confined to move in a circular ring of radius R and there is a solenoid (extremely long) of radius a < R, then, the angular momentum quantum number is modified by l eff = l − eΦ/2π (where Φ is the magnetic flux through the solenoid and e is the electric charge).…”
Section: Introductionmentioning
confidence: 99%
“…(19) can be written in terms of the eigenvalues of the z-component of the total angular momentum and the linear momentum operators: φ (r, ϕ, z) = e i(l+1/2)ϕ+ikz u (r), where k is a constant and l = 0, ±1, ±2, ±3, ±4 . .…”
mentioning
confidence: 99%
“…[26]. Again, the cosmic string spacetime was considered as a background to examine relativistic oscillators [27][28][29][30], quantum phases [31], and fermionic currents [32].…”
Section: Introductionmentioning
confidence: 99%